PENINGKATAN KETERAMPILAN MENULIS PUISI MENGGUNAKAN PENDEKATAN PEMBELAJARAN KONTEKSTUAL KOMPONEN PEMODELAN DI SEKOLAH DASAR - Azizah, Nur; Halidjah, Siti; Kresnadi, Hery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe research problem is whether the use of the component contextual learning approach can improve the poetry writing skills class III 15 South Pontianak State Elementary School?. The method used in this research is Classroom Action Research. The data collection technique used is the technique of observing and scrutinizing documents with a data collection tool that is the observation sheet of the teacher's ability to carry out learning and student learning outcomes complementing poetry. The subjects of the research were teacher and class III students 26 people. The results of the third cycle obtained are: 1) The ability of teachers to implement learning cycle I with a value of 2.61 with enough categories, the cycle II has increased from 0.43 to 3.04 which is included in both categories. While the cycle III increased by 0.89 to 3.93 and included in the very good category. 2) The poetry writing skills of students using the contextual learning approach component modeling cycle I 59.13 increased 14.42 in cycle II to 73.55 and in cycle III increased 19.23 to 92.78 which was included in the excellent category. So the conclusion by using the contextual learning approach component modeling in Indonesian learning can improve poetry writing skills. Therefore the component contextual learning approach can be used to improve students' poetry writing skills.Â Keywords: Component Modeling, Contextual Learning Approaches, Poetry Writing Skills